Is Edu-Tourism a Sustainable Option? A Case Study of Residents' Perceptions - Alipour, Habib; Fatemi, Hamed; Malazizi, Nahid (Mdpi, 2020)
In studies of the impact of tourism, considerable attention has been given to the attitudes and perceptions of host communities toward tourism. However, most of these studies have focused on tourism in general and on sporadic alternative tourism in particular. This study aims to fill a gap in the research literature by examining residents' perceptions of the economic, socio-cultural, and environmental sustainability of edu-tourism. It contributes to the limited literature on edu-tourism and to that on residents' perceptions of tourism in small island developing states. A sample of 300 (N = 300) residents was surveyed in the city of Famagusta in Northern Cyprus to investigate residents' attitudes toward the sustainability of edu-tourism. ANOVA and Cramer's V tests were applied to analyze the perceptions of residents of the social, economic, and environmental impacts of edu-tourism. The influence of the socio-demographic characteristics of the residents on their perceptions and attitudes was of these issues was also examined. The study revealed that there is a variety of attitudes among residents toward the sustainability of edu-tourism and that, although residents are generally positive about edu-tourism, attitudes toward its social and environmental sustainability are mixed.
Keywords: residents' perception; edu-tourism; community impacts; sustainability; edu-tourism destination